2010
DOI: 10.1038/jhh.2010.104
|View full text |Cite
|
Sign up to set email alerts
|

Olmesartan/amlodipine vs olmesartan/hydrochlorothiazide in hypertensive patients with metabolic syndrome: the OLAS study

Abstract: We studied the effects of treatment with olmesartan/amlodipine and olmesartan/hydrochlorothiazide on inflammatory and metabolic parameters (including new-onset diabetes as a secondary endpoint) in non-diabetic hypertensive patients with metabolic syndrome (MetS). A total of 120 patients with MetS and stage I and II hypertension were randomized to olmesartan 20 mg/amlodipine 5 mg or olmesartan 20 mg/hydrochlorothiazide 12.5 mg. If target systolic blood pressure (<140 mm Hg) was not reached, doses were doubled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 39 publications
2
52
0
Order By: Relevance
“…The anti-inflammatory effects of ARBs in hypertensive patients with microinflammation have been previously reported in the EUTOPIA study; olmesartan significantly reduced resting levels of hsCRP ( À15.1%, Po0.05), TNF-a ( À8.9%, Po0.02) and IL-6 ( À14.0%, Po0.05) within 6 weeks of treatment. 26 Similar findings for dihydropyridines have been reported in hypertensive patients with metabolic syndrome (MARCADOR and OLAS studies), 23,24 whereas there are no respective reports for non-dihydropyridines. Furthermore, perindopril has shown to have beneficial effects on inflammation indicators during exercise in patients with metabolic syndrome.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The anti-inflammatory effects of ARBs in hypertensive patients with microinflammation have been previously reported in the EUTOPIA study; olmesartan significantly reduced resting levels of hsCRP ( À15.1%, Po0.05), TNF-a ( À8.9%, Po0.02) and IL-6 ( À14.0%, Po0.05) within 6 weeks of treatment. 26 Similar findings for dihydropyridines have been reported in hypertensive patients with metabolic syndrome (MARCADOR and OLAS studies), 23,24 whereas there are no respective reports for non-dihydropyridines. Furthermore, perindopril has shown to have beneficial effects on inflammation indicators during exercise in patients with metabolic syndrome.…”
Section: Discussionsupporting
confidence: 69%
“…12,14,16 Antihypertensive treatment has been associated with beneficial effects on subclinical inflammation and thrombosis at rest and during exercise. [22][23][24][25][26] Nevertheless, comparative studies between different BPlowering agents have not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the well-written article by Martinez-Martin et al 1 entitled 'olmesartan/ amlodipine versus olmesartan/hydrochlorothiazide in hypertensive patients with metabolic syndrome: the OLAS Study'. The authors by using a parallel group, prospective open-label, blinded end-point design, have elegantly shown that both olmesartan combinations were well tolerated, effective in reducing blood pressure and additionally demonstrated benefit for different cardiorenal risk markers.…”
mentioning
confidence: 99%
“…3 In this context, many preclinical and small clinical studies with surrogate end points suggested that several antihypertensive drug categories, especially ARBs, angiotensin-converting enzyme inhibitors and calcium channel blockers may have benefits 'beyond BP control'. 7,8 The identification of such properties could help the selection of an optimal combination of antihypertensive drugs.…”
Section: Introductionmentioning
confidence: 99%